Épocas de consórcio de alho com beterraba perante três manejos do mato sobre a produtividade e o lucro - Mueller, Siegfried; Durigan, Julio Cezar [UNESP]; Banzatto, David Ariovaldo [UNESP]; Kreuz, Carlos Leomar (My University, 1998)
The research was carried out with intercropped cultivation of garlic and beet, in Caçador, SC, Brazil. Four seeding epochs for beet (0, 15, 30 and 45 days after garlic planting) and three management systems for weeds (with herbicides, without control and with frequent weeding) were tested. It was hoped to determine the effects of this intercropping, in time and space, seeking the benefits in .weed control, efficient land use, productivity, commercial quality, and profitability. The randomized block design was in split-plots. The epochs represented the plots, and the management, the subplots, with four replicates. Napromide at 750 g/ha did not cause symptoms of intoxication in the garlic plants, nor in the beet. All the treatments in epochs at the initiation of intercropping, in three management systems for weeds, presented efficient land use values greater than 1. The profitability of the intercropping of garlic and beet only became evident in the management involving frequent weeding; in all epochs, profits were greater than for the respective epochs of monoculture of beet and monoculture of garlic.

O presente trabalho trata do cultivo consorciado de alho e beterraba em Caçador, SC. Testaram-se quatro épocas de semeadura da beterraba (0, 15, 30 e 45 dias após o plantio do alho) perante três manejos de plantas daninhas (com herbicidas, sem controle e com capinas freqüentes). Objetivou-se determinar os efeitos desta consorciação, em tempo e espaço, visando aos benefícios no controle de plantas daninhas, ao uso eficiente da terra, à produtividade e sua qualidade comercial, e à rentabilidade. Utilizou-se o delineamento de blocos casualizados dispostos em parcelas subdivididas, sendo as épocas as parcelas, e os manejos, as subparcelas, e quatro, o número de repetições. O napropamide a 750 g/ha não causou sintomas de intoxicação às plantas de alho, nem às de beterraba. Todos os tratamentos de épocas de início de consórcio, dentro dos três manejos de plantas daninhas, apresentaram valores de uso eficiente da terra maiores do que 1. A rentabilidade do consórcio de alho e beterraba somente ficou evidente dentro do manejo com capinas freqüentes; em todas as épocas houve lucros maiores do que os que concernem às respectivas épocas de monocultivo de beterraba e do monocultivo de alho.
Benefits to yield and profits of garlic and beet intercropping under three weed management epochs
Keywords: Allium sativum; Beta vulgaris; Land equivalent ratio; Beta vulgaris subsp. vulgaris; Sativum